Evaluasi Pegaruh Perlakuan Nitridasi Gas Temperatur Tinggi Terhadap Pertumbuhan Butir Baja Tahan Karat 316L dan 316LVM - Agus Suprihanto (Jurnal Metalurgi dan Material Indonesia, 2018)
High temperature gas nitriding is a thermochemical treatment method that promises many advantages of improved mechanical properties and corrosion resistance of stainless steels. However, this treatment causes excessive grain growth. It is therefore necessary to evaluate the effect of such treatment on grain growth phenomenon on stainless steel. High temperature gas nitriding for 316L and 316LVM austenitic stainless steels has been successfully performed. The applied heating temperature is 1050, 1100 and 1200 0C with nitrogen gas pressure of 0.3 atm. The heating duration is set at 15 and 30 minutes. Observation of microstructure using metallographic microscope and grain measurement using particle analysis from ImageJ software. The test results showed that the grain growth constant (n) of 1.66, the growth rate of the grains (K) of 99 μm / s and the activation energy (Q) of 55.209 kJ / mol.